MORPHOLOGY OF RED BLOOD CELLS OF SUMATERAN RETICULATED PYTHONS - Sayuti, Arman; Asmilia, Nuzul; Anugrah, Rizki Ading; Rahmi, Erdiansyah; Roslizawaty, Roslizawaty; Hennivanda, Hennivanda (Buletin Veteriner Udayana, 2022)
Blood examination is an examination for further diagnosis, one of the methods for further diagnosis was to see the morphology of red blood cells. The aim of this study was to determine the morphology of red blood cells in the local Sumatran reticulated python ( M alayophyton reticulatus ). Fives samples of local Sumatran reticulated python ( M. reticulatus ) blood were collected through the ventral coccigea vein and made a blood smear. The results obtained were analyzed using descriptive methods, the results were that the morphology of red blood cells of Sumatran reticulated pythons  was oval in shape, had an oval to round nucleus, pink-purple cytoplasm and a deep purple nucleus. In addition, polychromatophilic red blood cells were also found with irregular nuclei, irregular cell shape, cell cytoplasm that was more faded than adult red blood cells and slightly smaller in size than adult erythrocytes. The conclusion is that the adult red blood cells of Sumatran reticulated pythons are oval in shape, has a nucleus, pink-purple cytoplasm and dark purple cell nucleus. The morphology of immature red blood cells is characterized by irregular nuclei, irregular cell shape and faded cytoplasm. Further research is needed to measure and count the number of the other blood cells.